Mediation in Malaysia: is it facilitative, evaluative or transformative? - Kamarudin, Abdul Rani; Ab Aziz, Norjihan (The West East Institute, 2014)
Mediation is a part of the alternative dispute resolution (ADR) process which is an alternative to litigation in the court proceeding. It is both informal and flexible dispute resolution in which the parties are free to participate in the process and come out with an amicable settlement. Mediation is an option for the disputants to reach a mutual agreement before the matter is brought to the court. The mediation process is speedy and the limitation of mediation award depends on kinds of disputes. The objectives of mediation are to reach an agreement to the dispute according to the needs and interests of the parties, to prepare the participants to accept the consequence of their decision and to reduce of the anxiety and other negative effects by assisting the participants to reach a consensual agreement. Mediation also helps to improve the relationship between the parties and is effective if the parties have a continuing relationship such as neighbours, family or business people. There are certain rules that have been enacted to govern matters concerning mediation and certain bodies are responsible to provide mediation services. This paper will analyse the implementation of mediation in Malaysia. The discussion will also include the process of mediation as provided under the existing regulations. Keywords: mediation, alternative dispute resolution (ADR), civil dispute.